Cruzamentos decoloniais com o nanorracismo na constituição dos corposterritórios das mulheres negras advogadas de Feira de Santana, Bahia - Melo, Daniele Cerqueira Britto de (2022)
Traveling along the paths of racism is a painful construction, but necessary to undermine its structures still strengthened by the ideologies of the caravels (MIRANDA, 2022). It even more hurts and tears, perhaps, to see such a tool of violence and achieve its invisible performance, which Achille Mbembe (2018) calls nanoracism. In order to understand what nanoracism actually is and how its functionality crosses the bodies-territories, I started with my own body as a black lawyer who resides and works mainly in the District of Feira de Santana, Bahia. The lawyers Dr. Lorena Aguiar, Dr. Mariana Rodrigues and Dr. Natanny Santos, all black and with main activity also in the city of Feira de Santana, Bahia. The foundations that support the bodies-territories of the women who wrote this research are composed of narratives peculiar to those whose skin color and gender are the impositions of colonialities. In order to understand how the violence of nanoracism is constituted on these bodies and its reflexes in the existences of these women, we initially resort to the refusal to use theoretical references constructed by what I define as the “perspective of the colonizer”, that is, socio-cultural politically and historically georeferenced by European seals or agreed with them. Here, I cite decoloniality as the theoretical anchor of this scientific research, as a critical and epistemological undressing brought by authors such as Catherine Walsh (2019), María Lugones ( In this way, the studies of Achile Mbembe (2017) Lélia Gonzalez (1988), Abdias do Nascimento (2016) and Frantz Fanon (2008) form the theoretical foundation for a broad and accurate view of the historical, social and political contexts that constituted the policies of enmity towards black bodies. -territory brought by the Bahians Muniz Sodré (1983) and Eduardo Oliveira Miranda (2018), whose (in) conclusions come together with the writings of Ochy Curiel (2020), Glória Andalzúa (2005), Maria Aparecida Bento (2002) and Nilma Lino Gomes (2017), who greatly contribute to the understanding of identities and crossings of race, gender and sexuality markers in the bodies of black women. tions and knowledge from the bodies-territories that build this research, the Sociopoetics of Jacques Gauthier (1999) was used as a methodological anchorage, which understands the body as a device for the production of knowledge, valuing and using all possible dimensions of the senses, this being the general objective of this work: to reveal how norracism crosses the body-territory of black women lawyers, which in turn are in line with the specific objectives, which are to describe the formative trajectory of black women lawyers in the law courses of Feira from Santana; to identify, through the criticality of decoloniality, how nanoracism is imposed on black women and lawyers in the academic and professional environment and to show the nanoinsurgencies of these women during their formative trajectories and professional performance, since it is inherent to our existence to refuse to keep in our minds and liberties the shackles of subalternities.